High number of HPAI H5 virus infections and antibodies in wild carnivores in the Netherlands, 2020–2022 - Chestakova, Irina V.; van der Linden, Anne; Bellido Martin, Beatriz; Caliendo, Valentina; Vuong, Oanh; Thewessen, Sanne; Hartung, Tijmen; Bestebroer, Theo; Dekker, Jasja; Jonge Poerink, Bob; Gröne, Andrea; Koopmans, Marion; et al. (Emerging microbes & infections, 2023)
In October 2020, a new lineage of a clade 2.3.4.4b HPAI virus of the H5 subtype emerged in Europe, resulting in the largest global outbreak of HPAI to date, with unprecedented mortality in wild birds and poultry. The virus appears to have become enzootic in birds, continuously yielding novel HPAI virus variants. The recently increased abundance of infected birds worldwide increases the probability of bird-mammal contact, particularly in wild carnivores. Here, we performed molecular and serological screening of over 500 dead wild carnivores and sequencing of RNA positive materials. We show virological evidence for HPAI H5 virus infection in 0.8%, 1.4%, and 9.9% of animals tested in 2020, 2021, and 2022 respectively, with the highest proportion of positives in foxes, polecats and stone martens. We obtained near full genomes of 7 viruses and detected PB2 amino acid substitutions known to play a role in mammalian adaptation in three sequences. Infections were also found in without neurological signs or mortality. Serological evidence for infection was detected in 20% of the study population. These findings suggests that a high proportion of wild carnivores is infected but undetected in current surveillance programmes. We recommend increased surveillance in susceptible mammals, irrespective of neurological signs or encephalitis.